Comparative evaluation of bioactivity, fluoride release, shear bond strength, and compressive strength of conventional glass ionomer cement incorporated with three inorganic bioactive nanoparticles: An experimental analysis - Pranjali Mahesh Pokharkar; N D Shashikiran; Namrata Gaonkar; Sachin Gugawad; Savita Hadakar; Sonali Waghmode (Wolters Kluwer Medknow Publications, 2022)
Background: Over the course of four decades, the bioactive materials have changed. They have become more specialized, more manageable, possessing superior qualities. Thus, it should be encouraged to conduct ongoing research to improve these materials even further in order to meet the growing clinical and restorative needs. Aims and Objectives: To evaluate and compare bioactivity, fluoride release, shear bond strength and compressive strength of conventional GIC incorporated with three inorganic bioactive nanoparticles. Materials and Methods: For the study, total of 160 samples were included. The samples were divided in four groups (40 samples per group) i.e. 3 wt% of forsterite (Mg2SiO4) (Group 2), wollastonite (CaSiO3) (Group 3) and niobium pentoxide (Nb2O5) (Group 4) nanoparticles incorporated into GIC (Group 1). The bioactivity (FEG-SEM and EDX analysis), fluoride release (ion-selective electrode), shear bond strength testing (UTM followed by evaluation under stereomicroscope) and the compressive strength (UTM) was checked for each group. Results: Wollastonite nanoparticles (3wt %) incorporated to GIC showed maximum increase in the apatite crystal formation,Ca and P content and highest fluoride release. Mean shear bond strength was highest in niobium pentoxide nanoparticles (3wt %) incorporated to GIC while mean compressive strength was highest in forsterite nanoparticles (3wt %) added to GIC. Conclusion: Positive results were observed which showed increase in the bioactivity alongwith enhancement of the fluoride release, shear bond strength and compressive strength but further research on these materials is warranted before its use in clinical practice.